RESULTS OF RESTORATIVE OPERATIONS USING MODIFIED METHOD OF FORMATION OF TEMPORARY LOOP INTESTINAL STOMAS - V. I. Pomazkin (Вестник хирургии имени И.И. Грекова)
The article estimated the results of excision of temporary loop colo- and ileostomas using method of their formation with fixation of parietal peritoneum to aponeurosis of abdominal external oblique muscle in 18 patients. The authors concluded that the formation of temporary loop stoma with fixation of parietal peritoneum to aponeurosis had many advantages and could improve the results of the restorative operation.